2013
DOI: 10.1051/0004-6361/201321979
|View full text |Cite
|
Sign up to set email alerts
|

X-shooter spectroscopy of young stellar objects

Abstract: Context. Traditionally, the chromospheres of late-type stars are studied through their strongest emission lines, Hα and Ca ii HK emission. Our knowledge on the whole emission line spectrum is more elusive as a result of the limited spectral range and sensitivity of most available spectrographs. Aims. We intend to reduce this gap with a comprehensive spectroscopic study of the chromospheric emission line spectrum of a sample of non-accreting pre-main sequence stars (Class III sources). Methods. We analyzed X-sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
72
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 73 publications
(88 reference statements)
16
72
2
Order By: Relevance
“…11). Stelzer et al (2013) found a similar trend analyzing a sample of pre-MS low-mass stars in the 2500-4500 K temperature range. Conversely, Kendall's correlation test cannot reject the hypothesis that the slope of the flux-flux relationship is independent of the average level of activity, or the metallicity of the star.…”
Section: Ca II Handk Vs Hαsupporting
confidence: 59%
“…11). Stelzer et al (2013) found a similar trend analyzing a sample of pre-MS low-mass stars in the 2500-4500 K temperature range. Conversely, Kendall's correlation test cannot reject the hypothesis that the slope of the flux-flux relationship is independent of the average level of activity, or the metallicity of the star.…”
Section: Ca II Handk Vs Hαsupporting
confidence: 59%
“…This behavior is more evident in the B component. The fluxes we measured are also close to the maximum values found by Stelzer et al (2013) in a sample of Class III stars belonging to three young associations.…”
Section: Chromospheric Activitysupporting
confidence: 87%
“…The Balmer decrement, F Hα /F Hβ , is lower than two for both stars, like the minimum values observed by Stelzer et al (2013) for stars of comparable T eff , and it is close to the solar plage values (see their Fig. 13).…”
Section: Chromospheric Activitysupporting
confidence: 81%
See 2 more Smart Citations